Development of Lokal Wisdom-Based “Daily Say’s” Learning Media in English Learning for Grade 4 of Trembes State Elementary School - Mufaricha Ulia Anjani; Suttrisno; Nurul Mahruzah Yulia (Journal of Practice Learning and Educational Development, 2025)
The lack of innovation learning media at SD Negeri Trembes causes low interest and understanding of students towards English subjects, low knowledge of students towards local wisdom in their environment is also a problem that needs attention. This study aims to develop learning media "Daily Says" based on local wisdom, find out the results of its development, measure the effectiveness of its use in learning English. The method used is Research and Development with the ADDIE model which analysis, design, development, implementation, evaluation. The subjects of the study were 22 4th grade students of SD Negeri Trembes. The validation results from material experts obtained 96%, media experts 96%, and language experts 97.5% with each category "very feasible". The results of the trial showed an increase in student learning outcomes with a pre-test percentage of 59.5% while the post-test was 87.7%, with an N-Gain value of 0.71 which is included in the high increase category. Based on the results of the study, it can be concluded that the process of developing learning media "Daily Say's" based on local wisdom took place systematically and in accordance with student needs. According to experts, this learning media is stated to be very suitable for use in the learning process. In addition, the learning media has been proven effective in helping students understand English learning material "What Are You Doing" and recognize local wisdom in their surroundings.